Determinación de la doble reacción de aglutinación en pacientes neonatos, mediante la aplicación de la técnica en gel en prevención de complicaciones transfusionales al requerir la administración de componentes plasmáticos en el Hospital General docente de riobamba durante el período enero a junio de 2015. - Quishpe Yambay, Daisy Elizabeth (2015)
This research work was conducted at the Department of Transfusion Medicine Provincial General Teaching Hospital in Riobamba, as the study population was considered to neonatal patients with the aim of preventing transfusion complications by identifying them blood characterizations with results double population reaction. This means in technical terms Immunohaematology; discrepancies in their results and according to laboratory techniques used might this involve an error in the conclusion of its outcome and if the patient requires transfusions, is increased by this result a complication that generate adverse effects or reactions transfusion, Applying the typing technique gel if could prevent transfusion reactions by 100% in 8 neonates patients requiring administration of plasma components, to achieve this was initiated with the embodiment of the typing test gel to blood samples infants who gave results double agglutination reaction and their mothers to correlate blood group, blood samples were also requested, in which it was concluded that the blood sample were contaminated with maternal blood so it had the effect of double population reaction to this result was made typifications tube which reports a maternal blood tipi's not the infant and if working alone with this result we could generate transfusion reactions if warranted transfusion plasmas.